Die Einzelhandelszentralität westdeutscher Städte: Ein Beitrag zur Methodik der Zentralitätsmessung - Giese, Ernst (ERDKUNDE, 1996)
Within the regional planning system of the Federal Republic of Germany, the central place model is used as a framework for the development of the settlement structure. The political relevance of the central place model is due to its embodiment within German regional planning laws (i.e. Bundesraumordnungsgesetz). Therein, it is postulated that the central place model will provide a long-term guide for the spatial structure. The central place model was originally developed by CHRISTALLER (1933) within the framework of a free enterprise economy. With today's mobile society, however, the central place model often establishes a barrier for the development of the settlement structure. In regional policy practice, the model sometimes creates a hinderance, as opposed to a stimulus, for economic development. This is usually justified with reference to the regional planning laws, as is the ease when large retail firms are forced to locate in high-order central places. Due to the changes of societal and economic conditions since CHRISTALLER'S work, the central place model no longer seems to provide an adequate framework for the development of the settlement structure. There is, however, no other model available which could be used as an alternative basis for regional planning. It is, thus, unrealistic to expect that the central place model will be abandoned by the German system of regional planning. This proves to be a severe dilemma: the central place model is, on the one hand, inadequate and should be replaced by a better concept. On the other hand, an improved model does not yet exist to replace it. Regional planning agencies have adjusted to this situation in that they have developed their own indicators and methods which essentially validate the existing settlement structure, thereby avoiding major changes. This practice has, in turn, undermined the sub. stance of the original model. This article will reconsider the terminology and methodology of central place concepts and will especially identify and discuss methodological problems. The analysis will be based on an investigation of the retail trade centrality of all cities in western Germany that have more than 50,000 inhabitants (n = 157). It is aimed to develop and test a simple method through which the retail trade centrality of German cities can be determined.